Integrasi Pandangan Hidup Pengarang dalam Novel Para Priyayi untuk Pembelajaran Nilai Pendidikan dan Mobilitas Sosial di Perkuliahan Apresiasi Prosa UIN Sayyid Ali Rahmatullah Tulungagung - Muyassaroh (Universitas Insan Budi Utomo, 2025)
Umar Kayam’s novel Para Priyayi presents the social dynamics of Javanese society, particularly the role of education in class mobility. Through its characters, the narrative illustrates how education serves as both a means of social transformation and a tool for legitimizing priyayi status. The author's worldview is embedded in the story structure and character development, emphasizing education as a cultural and ideological force. Employing a descriptive-qualitative approach, the analysis adopts structural and intertextual frameworks to reveal the interplay between the literary text, its socio-historical context, and the author’s ideological stance. Findings indicate that Umar Kayam consistently positions education as a key pillar of social change, while subtly critiquing unequal access to educational opportunities. These values are highly relevant to the teaching of prose appreciation in higher education, offering literature as a reflective medium to foster students’ social awareness, cultural understanding, and character development. In this context, literature functions not merely as an aesthetic object, but also as a pedagogical instrument that is contextual and transformative